Gambaran kanker endometrium yang dirawat di RSUP Prof. Dr. R.D. Kandou Manado periode 2013 – 2015 - Tulumang, Jeinyver A.; Loho, Maria F.; Mamengko, Linda M. (e-CliniC, 2016)
Abstract: Endometrial cancer is a malignant tumor of primary endometrial epithelium, usually with glandular differentiation and potentially involves the myometrium and spreads widely. It is also a common gynecologic cancer. The cause is not known for certain, but there are several factors causing this endometrial cancer. This study aimed to describe endometrial cancer treated at Prof. Dr. R.D. Kandou Hospital Manado. This was a descriptive retrospective study using data of endometrial cancer patient medical record. From the 36 cases of endometrial cancer, aged ≥51 was obtained as many as 24 people (66.67%), and this cancer increased in multiparous women and obesity; as many as 11 people (30.56%) had postmenopausal endometrial cancer. Most comorbidities were hypertension (13 cases, 36.11%) Most frequent type of endometrial cancers was endometrioid adenocarcinoma (19 cases, 52.78%). Treatments applied were medicamentous therapy, surgery and chemotherapy. The most frequent stage was stage II (8 cases, 22.23%).Keywords: endometrial cancerAbstrak: Kanker endometrium adalah tumor ganas epitel primer diendometrium, umumnya dengan diferensiasi glandular dan berpotensi mengenai miometrium dan menyebar jauh; juga merupakan kanker ginekologi yang sering terjadi. Penyebabnya belum diketahui secara pasti, namun terdapat beberapa faktor yang menyebabkan terjadinya kanker endometrium. Penelitian ini bertujuan untuk mengetahui gambaran kanker endometrium yang dirawat di RSUP Prof. dr. R.D. Kandou Manado. Jenis penelitian deskriptif retrospektif, dengan cara mengumpulkan data rekam medik pasien kanker endometrium. Dari 36 kasus kanker endometrium, didapatkan usia ≥51tahun sebanyak 24 orang (66,67%), meningkat pada wanita multipara dan obesitas, sebanyak 11 orang (30,56%) mengalami kanker endometrium pascamenopause. Penyakit penyerta terbanyak yaitu hipertensi berjumlah 13 orang (36,11%). Jenis sel kanker terbanyak yaitu endometrioid adenokarsinoma berjumlah 19 orang (52,78%). Penanganan yang diberikan berupa terapi medikamentosa, operasi dan kemoterapi. Stadium terbanyak yaitu stadium II berjumlah 8 orang ( 22,23%).Kata kunci: kanker endometrium